PERAN DAN PENGARUH FATWA MUI DALAM ARUS TRANSFORMASI SOSIAL BUDAYA DI INDONESIA - Muhammad Maulana Hamzah (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2017)
Social change as a result of cultural dynamics often leads to friction in society. Islam as a universal religion with specific guidance based on the Quran and hadith has the role of scholars to translate the socio-cultural transformation in the form of fatwa. This research explains the role and influence of fatwa MUI on socio-cultural change in Indonesia refers to 47 fatwa MUI in socio-cultural field. Descriptive-qualitative method with deepening of literature study on socio-historical approach is used to answer the questions above. The result, there are 8 causes of socio-cultural change in Indonesia, namely the way of thinking, population growth, interaction with other communities and nations, new discoveries, technology, disasters and conflicts in the community. Although the law position of fatwa is not binding, some of its influence are quite significant such as the people involvement in the program KB, the development of sharia financial, and the correction to aqidah of ummah in the face of Christmas. â€“(Perubahan sosial sebagai hasil dinamika budaya sering menimbulkan gesekan di masyarakat. Islam sebagai agama universal dengan panduan spesifik berdasarkan Quran dan hadis memerlukan peran ulama untuk menerjemahkan transformasi sosio-kultural dalam bentuk fatwa. Penelitian ini menjelaskan peran dan pengaruh fatwa MUI terhadap perubahan sosio-kultural di Indonesia mengacu pada 47 fatwa MUI di bidang sosio-kultural. Metode deskriptif-kualitatif dengan memperdalam studi literatur tentang pendekatan sosio-historis digunakan untuk menjawab pertanyaan di atas. Hasilnya, ada 8 penyebab perubahan sosio-kultural di Indonesia, yaitu cara berfikir, pertumbuhan penduduk, interaksi dengan masyarakat dan bangsa lain, penemuan baru, teknologi, bencana dan konflik di masyarakat. Meski posisi hukum fatwa tidak mengikat, beberapa pengaruhnya cukup signifikan seperti keterlibatan masyarakat dalam program KB, pengembangan keuangan syariah, dan koreksi terhadap aqidah ummat saat menghadapi natal.)–